Impact of urban green infrastructure on ecosystem services: A systematic review - Yunong Yao; Hua Zheng; Zhiyun Ouyang; Cheng Gong; Jian Zhang; Lingxiao Ying; Zhi Wen (Ecological Indicators, 2025)
Urban green infrastructure (UGI) plays a key role in providing various ecosystem services (ES), which contribute to urban residents’ well-being and sustainable city management. However, the specific ES influenced by different types of UGI and the key level of UGI that impact urban ES are not yet fully understood. We identified 22 ecosystem services (ES) based on the Common International Classification of Ecosystem Services and categorized urban green infrastructure (UGI) into six types. We then reviewed 235 publications to examine the relationships between UGI type, level, and ES at different levels. We found that: (1) The research predominantly focuses on “parks and (semi-)natural green spaces” and “green structures connected to gray infrastructure”. (2) At the landscape and community levels, UGI primarily enhances cultural services, influenced mainly by accessibility and area. (3) At the community and individual levels, UGI mainly supports regulating services, with key structural factors being vegetation cover, species diversity, and tree diameter at breast height (DBH) and age, respectively. The findings highlight the importance of considering differences in ES improvement across various levels of urban UGI design. These insights are valuable for the construction and management of UGI, helping to enhance urban resilience, improve ES, and elevate the overall living environment.